Modifications and Further Development of the Original Nuss Procedure: Blessing or Curse? - Kelly Jr, Robert Edward (European Journal of Pediatric Surgery, 2018)
The procedure introduced by Donald Nuss in 1997 for the treatment of pectus excavatum at the American Pediatric Surgical Association meeting has now been adopted by pediatric, thoracic, and plastic surgeons around the world. Rather than resection of the costal cartilages and sternal fracture, which had been standard practice for decades, he advocated using a metal bar to push the sternum into position. Reasoning that the chest wall of children is very flexible, he felt that resection was unnecessary. Since that time, medical centers from around the world have reported their experience with the procedure. There is now robust evidence of its safety and efficacy. As the Nuss procedure has become a standard treatment, indications for operation have expanded, and numerous modifications have been introduced. Some of these were intended to improve upon the original procedure, and others to adapt it to new circumstances, such as use in adults whose chest is not as flexible. This report reviews those modifications.
Keywords: pectus excavatum; pectus carinatum; Nuss procedure; modifications to Nuss procedure; technique of operation